Inflammation and Skeletal Muscle Wasting During Cachexia - Webster, Justine M.; Kempen, Laura J. A. P.; Hardy, Rowan S.; Langen, Ramon C. J. (Frontiers in Physiology, 2020)
Cachexia is the involuntary loss of muscle and adipose tissue that strongly affects mortality and treatment efficacy in patients with cancer or chronic inflammatory disease. Currently no specific treatments or interventions are available for patients developing this disorder. Given the well-documented involvement of pro-inflammatory cytokines in muscle and fat metabolism in physiological responses and in the pathophysiology of chronic inflammatory disease and cancer, considerable interest has revolved around their role in mediating cachexia. This has been supported by association studies that report increased levels of pro-inflammatory cytokines such as TNF-α and IL-6 in some, but not all, cancers and in chronic inflammatory diseases such as COPD and rheumatoid arthritis. In addition, preclinical studies including animal disease models have provided a substantial body of evidence implicating a causal contribution of systemic inflammation to cachexia. The presence of inflammatory cytokines can affect skeletal muscle through several direct mechanisms, relying on activation of the corresponding receptor expressed by muscle, and resulting in inhibition of muscle protein synthesis, elevation of catabolic activity through the ubiquitin-proteasome system (UPS) and autophagy, and impairment of myogenesis. Additionally, systemic inflammatory mediators indirectly contribute to muscle wasting through dysregulation of tissue and organ systems, including GCs via the hypothalamus-pituitary-adrenal (HPA) axis, the digestive system leading to anorexia-cachexia, and alterations in liver and adipocyte behaviour, which subsequently impact on muscle. Finally, myokines secreted by skeletal muscle itself in response to inflammation, have been implicated as autocrine and endocrine mediators of cachexia, as well as potential modulators of this debilitating condition. Whilst inflammation has been shown to play a pivotal role in cachexia development, further understanding how these cytokines contribute to disease progression is required to reveal biomarkers or diagnostic tools to help identify at risk patients, or enable the design of targeted therapies to prevent or delay the progression of cachexia.